1968
DOI: 10.1177/030098586800500112
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Evidence for the Viral Etiology of Feline Infectious Peritonitis

Abstract: Filtration studies indicate that the causative agent of feline infectious (fibrinous) peritonitis is less than 200 m μ in smallest dimension. Viral particles 94 m μ in diameter, within and budding into the endoplasmic reticulum of the mesothelial cells in areas of inflammation, were found by electron microscopy and may be the etiologic agent. No bacterium or mycoplasma was cultured from peritoneal exudate, nor identified in affected tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
2

Year Published

1978
1978
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 1 publication
1
14
1
2
Order By: Relevance
“…Specific peritoneal sonographic features have not been well described in FIP, however, in the author's experience (DT), abnormal hypoechoic tissue, which typically appears as contiguous thickened sheets, can be seen dissecting throughout the mesentery and lining peritoneal surfaces. This material is thought to correspond to the histologically reported fibrinous serositis/peritonitis described with FIP . Carcinomatosis and FIP have similar mesenteric sonographic findings to lymphomatosis, however, the index of suspicion for lymphomatosis should increase in the presence of either a focally diffuse nonobstructive intestinal mass or focally diffuse eccentric gastric mass with loss of wall layering.…”
Section: Discussionsupporting
confidence: 59%
“…Specific peritoneal sonographic features have not been well described in FIP, however, in the author's experience (DT), abnormal hypoechoic tissue, which typically appears as contiguous thickened sheets, can be seen dissecting throughout the mesentery and lining peritoneal surfaces. This material is thought to correspond to the histologically reported fibrinous serositis/peritonitis described with FIP . Carcinomatosis and FIP have similar mesenteric sonographic findings to lymphomatosis, however, the index of suspicion for lymphomatosis should increase in the presence of either a focally diffuse nonobstructive intestinal mass or focally diffuse eccentric gastric mass with loss of wall layering.…”
Section: Discussionsupporting
confidence: 59%
“…Feline infectious peritonitis represents an uncommon secondary form of a common i n a p p a r e n t or mild p r i m a r y illness of cats (15). The F I P agent has strong morphologie and physical similarities to known coronaviruses (8,16,24,26). A possible antigenic relationship between feline infectious peritonitis virus (FIPV) and the transmissible gastroenteritis virus (TGEV) of swine has been recently reported (13,19,25), which further supports the assumption t h a t F I P V is a coronavirus.…”
Section: Introduetionmentioning
confidence: 71%
“…This has been demonstrated in cultivated macrophages (Jacobse-Geels and Horzinek, 1983) and by experimental studies which showed that aerosol application of FIPV results in infection of macrophages and persistent cell-associated viremia (Weiss and Scott, 1981a, b). Electron microscopical examinations demonstrated virus replication in peritoneal macrophages, mesothelial cells, and degenerating macrophages in inflammatory lesions (Zook et al, 1968;Hayashi et al, 1978;Weiss and Scott, 1981b). However, in our study, even activated mesothelial cells did not stain positive for coronavirus antigen.…”
Section: Discussionmentioning
confidence: 97%